Relatório de Estágio Profissional - "Ser professor: do sonho à realidade da escola" - Francisca Pereira Machado (2018)
The professional stage is characterized by being the culmination of a cycle of studies, and which in turn represents the beginning of a new stage, where we put into practice all the knowledge acquired along the academic path. This is characterized by being a year full of challenges and doubts, and the analysis of them will be central to the constant learning of the profession. This document is the mirror of the year of a student, where it shows all the inherent wealth of the pedagogical practice and the reality of the school, and aims at an in-depth reflection on my performance in this year full of emotions. This document was prepared within the scope of the professional stage, a curricular unit present in the second year of the Master's Program in Teaching Physical Education in Basic and Secondary Education, of the Faculty of Sport of the University of Porto. This document is organized in six chapters. The first chapter refers to the "Introduction", where it refers to the framework of the professional stage and the purpose of the realization of this document. The second chapter deals with the "Personal Framework", where I make a presentation about my path up to here, then in the third chapter I talk about the "Institutional Framework", where the characteristics of the internship are explained. The fourth chapter refers to the "Operational Framework", where there is a subdivision into three areas. Area 1, "Organization and Management of Teaching and Learning", Area 2, "Participation in school and Involvement with the Community", and finally in Area 3, "Professional Development", which reflects several aspects that contributed to my training. In chapter five, we can find the "Research Study" developed during the academic year, referring to the shared group of the stage nucleus, aiming at the improvement of the psychomotor, conditional and coordinating capacities. Finally, the sixth chapter, "Conclusions and Perspectives for the Future," reflects on the most striking experiences and prospects for the future, after this remarkable year.